The relationship of CH, CB, and CR chondrites: Constraints from trace elements and Fe-Ni isotope systematics in metal. (1st September 2021) - Weyrauch, M.; Zipfel, J.; Weyer, S.
Abstract: Due to similarities in chemical composition and common Cr, Ti, N and O isotope trends, the metal-rich CR, CH and CB chondrites, often referred to as CR clan chondrites, are thought to be related to each other. This study aims to shed light on this relationship by the investigation of Fe and Ni isotope and trace element compositions of metal grains from CR and CH chondrites, in order to compare the results with previously reported data from CB chondrite metal. In situ trace element and Fe and Ni isotope analyses were conducted by femtosecond-laser ablation-(multicollector-)inductively coupled plasma-mass spectrometry (fs-LA-(MC-)ICP-MS). Furthermore, bulk CB metal and silicate separates were analyzed by solution MC-ICP-MS. Chemical compositions of metal grains in metal-rich chondrites are depleted in moderately volatile siderophile elements relative to the solar values with the exception of Pd. Such element abundance patterns are consistent with models of incomplete condensation from a gas with solar composition. Both, zoned and unzoned metal grains from CH and CB chondrites display very similar Fe and Ni isotopes compositions, indicating they likely formed within the same event, during non-equilibrium fractional condensation from an impact-induced vapor plume. This scenario is also supported by non-equilibrium Fe isotope signatures between bulk CB metal and silicate. Zoned metal grains likely formed in the fast-cooling outer shell region of the plume and are dominated by kinetic fractionation, resulting in isotopically light cores, while unzoned metal grains condensed under nearly equilibrium conditions, likely in the slow-cooling interior of the plume. Variability in Fe and Ni isotope compositions among different unzoned grains may be explained by (1) a kinetic component during their condensation and/or (2) evaporation and condensation-driven reservoir effects in the plume, which resulted in light and heavy isotope signatures, respectively. Textural differences between CH and CBb are most pronounced in the mean grain size, which may be attributed to grain-size sorting. Such a process could also explain the lack of zoned metals in CBa chondrites, as zoned metal grains in CBb and CH chondrites are by more than a magnitude smaller than the mean metal grain size of CBa chondrites. In CR chondrites, metal within chondrules likely formed by fractional condensation from a solar type gas followed by subsequent melting leading to equilibration with chondrule silicates. Larger isolated metal grains from the matrix are less processed, and apparently escaped silicate equilibration. Those metal grains are indistinguishable from unzoned grains in CH and CB chondrites in trace elements and Fe and Ni isotopic compositions albeit with a slightly narrower compositional range. Based on these findings we conclude that metal precursors in CR chondrites are strongly related to unzoned metal in CH, and CB chondrites and possibly share a common origin. This metal component would be smallest in CR chondrites, larger in CH and dominant in CB chondrites which is also consistent with age constraints and isotopic anomalies observed in CR clan chondrites.